Paresthesia: A Review of Its Definition, Etiology and Treatments in View of the Traditional Medicine - Ahmad Emami, Seyed; Sahebkar, Amirhossein; Javadi, Behjat (Current Pharmaceutical Design, 2016)
Objective: To search major Islamic Traditional Medicine (ITM) textbooks for definition, etiology and medicinal plants used to manage ‘khadar’ or ‘paresthesia’, a common sensory symptom of multiple sclerosis (MS) and peripheral neuropathies. In addition, the conformity of the efficacy of ITM-suggested plants with the findings from modern pharmacological research on MS will be discussed. Methods: Data on the medicinal plants used to treat ‘khadar’ were obtained from major ITM texts. A detailed search in PubMed, ScienceDirect, Scopus and Google Scholar databases was performed to confirm the effects of ITM-mentioned medicinal plants on MS in view of identified pharmacological actions. Results: Moringa oleifera Lam., Aloe vera (L.) Burm.f., Euphorbia species, Citrullus colocynthis (L.) Schrad., and Costus speciosus (Koen ex. Retz) Sm. are among the most effective ITM plants for the management of ‘khadar’. Recent experimental evidence confirms the effectiveness of the mentioned plants in ameliorating MS symptoms. Moreover, according to ITM, prolonged exposure to cold and consuming foodstuff with cold temperament might be involved in the etiopathogenesis of MS. Conclusions: The use of traditional knowledge can help finding neglected risk factors as well as effective and safe therapeutic approaches, phytomedicines and dietary habits for the management of paresthesia and related disorders such as MS.
Keywords: khadar